2015
DOI: 10.1080/00220388.2014.984898
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Chain Migration: Longitudinal Evidence from Bosnia and Herzegovina

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…Beyond these theoretical approaches, the few empirical studies on the link between migration and remittances find that receiving remittances has a positive impact on migration intentions, at least in Morocco (van Dalen et al, 2005), Bosnia-Herzegovina (Dimova and Wolff, 2009), Fiji and Tonga (Leeves, 2009) and Eastern Europe and Central Asia countries (Naiditch and Vranceanu, 2010).…”
Section: Remittances and Migration: A Literature Reviewmentioning
confidence: 97%
“…Beyond these theoretical approaches, the few empirical studies on the link between migration and remittances find that receiving remittances has a positive impact on migration intentions, at least in Morocco (van Dalen et al, 2005), Bosnia-Herzegovina (Dimova and Wolff, 2009), Fiji and Tonga (Leeves, 2009) and Eastern Europe and Central Asia countries (Naiditch and Vranceanu, 2010).…”
Section: Remittances and Migration: A Literature Reviewmentioning
confidence: 97%
“…In Turkey, 36 percent of remittance-receiving individuals intended to migrate, whereas only 24 percent of those who did not receive remittances had that intention (van Dalen, Groenewold, and Fokkema, 2005). Using longitudinal data, Dimova and Wolff (2009) examined the effect of remittances on chain migration in Bosnia and Herzegovina. Individuals from households that received remittances were 32 percent more likely to plan to migrate than those that non-receiving households.…”
Section: Social Capital Theorymentioning
confidence: 99%
“…Furthermore, when participants were asked if they intended to migrate that year, those who received remittances were over two times more likely to say yes. Healthy, young, highly-educated participants who received remittances were the most likely to intend to migrate (Dimova and Wolff, 2009). Using cross-sectional data from Fiji and Tonga, Leeves (2009) examined the relationship between the receipt of remittances and intentions to migrate within the following two years.…”
Section: Social Capital Theorymentioning
confidence: 99%
“…Reverse causality can be due to various reasons. By suggesting the success of migrants and relaxing liquidity constraints, remittances may impact the realisation of emigration prospects (van Dalen et al., ; Dimova and Wolff, ). A large number of empirical studies have also identified an effect of remittances on education choices (Cox‐Edwards and Ureta, ), suggesting that the educational structures of the migrant and non‐migrant populations are endogenous.…”
Section: Empirical Analysismentioning
confidence: 99%